Mapeamento das Escolas Infantis da Rede Municipal de Maceió para recurso coletivo - Rodrigo Vanderlan Nascimento; Júlia Cristina Soares Rodrigues; Pedro Henrique Simonard; Jesana Batista Pereira; Ajibola Isau Badiru (Confins)
This article deals with the integrated analysis of the school image as a collective resource, precisely because it is incipient by socio-environmental concerns given the influences and urban conditions, requiring greater attention for interdisciplinary parameters that are recommended to be equated at any teaching level. This research has the general objective of contemplating the municipal network of kindergartens, analyzing its coverage of 58 units distributed in the city of Maceió, state of Alagoas. From the empirical database construction, using checklist with a set of analog parameters, the data collected in the ArcGIS virtual environment were organized and processed, in which geotechnology provided the development of image maps by the Geographic Information System (GIS). Schools as space agencies are influenced by eight socio-environmental conditions: identity, location, functionality, intensity, resilience, potentiality, personality and criticality, mapped as a collective resource for the creation of knowledge about the totality of the space occupied. The synthesis maps that were generated serve to strengthen the institutional infrastructures of education, as well as new postures necessary for mobilization, school management and more sustainable planning, considering their integrated system to the local endogenous development of the territory.